Students’ use of Facebook for peer-to-peer learning - Dalsgaard, Christian (Proceedings of the International Conference on Networked Learning, 2014)
This paper presents the findings from an empirical study of five non-institutional Facebook groups created and managed by students in Danish upper secondary schools. The objective of the paper is to study educational potentials of Facebook with a focus on students’ self-organized academic communication. The empirical study includes a questionnaire distributed to 2035 students and 182 teachers and a qualitative analysis of communication spanning more than two years within each of the five Facebook groups. The study provides an insight into how students communicate about school work without the participation of teachers. The findings from the questionnaire show that whereas students and teachers primarily use institutional learning management systems to communicate among each other, students clearly prefer social media when they communicate with fellow students. The study shows that students’ school-related use of Facebook is widespread. More than 80 % of the students in the questionnaire specified that they use Facebook as a communication tool in relation to their school work. Further, 67 % of the students state that they “almost all the time” or “often” use social media (which is primarily Facebook) to help each other with homework and other school-related work. Only 11 % answer “rarely” or “never”. Based on the findings from the questionnaire, a qualitative analysis of student communication in five Facebook groups is completed. The paper presents findings from the study that demonstrates students’ extensive use of Facebook groups to help each other with all kinds of school-related matters, including issues relating directly to academic subjects. The study rejects the claims that students do not wish to use Facebook for school-related activities. The empirical study demonstrates that students are using Facebook groups to help each other with all kinds of school-related matters, including issues relating directly to academic subjects. Based on the findings from the study, the paper concludes that there is an educational potential of Facebook groups in supporting peer-to-peer learning between students. The study has identified a usage of Facebook among students that differs from studies of Facebook being used as a learning management system, where the teachers is present and manages the groups.